Controlled oxygen therapy and pulmonary heart failure. Issue 5 (September 1971) - Ude, A. C.; Howard, P.
Abstract : One hundred and sixty-six episodes of pulmonary heart failure were treated in 40 patients with chronic bronchitis. The natural history of the disease is described when controlled oxygen is the principal therapy. Only eight episodes of heart failure required intermittent positive pressure ventilation. Despite careful attention to the details of the controlled oxygen technique the longterm survival of these patients was no better than during an earlier period when oxygen was either not given or administered intermittently for short periods. The implications of this finding are discussed.